Plant Growth Promoting Actinobacteria, the Most Promising Candidates as Bioinoculants? - Boukhatem, Zineb Faiza; Merabet, Chahinez; Tsaki, Hassini (Frontiers in Agronomy, 2022)
Plant Growth Promoting Bacteria (PGPBs) are a strong ally for sustainable agriculture. They offer an interesting alternative to chemical fertilizers and pesticides. Many microorganisms have been widely documented for their PGPR traits, but actinobacterial microbes which were increasingly documented solely these two past decades for their promoting plant growth ability. Their action on plant health and yield could be either direct or indirect or both. This review will deal with what have been published on Actinobacteria PGP traits, highlighting the involved mechanisms to reveal their strong potential as microbial fertilizers. On the other hand, possible strategies to encourage Actinobacteria use as bioinoculants will be discussed.